TRANSLATION SHIFTS IN INDONESIAN VERSION OF SHELDON’S WINDMILLS OF THE GODS - Ira Miranti (UIN Raden Mas Said Surakarta, 2017)
This article discusses one of the linguistic challenges discovered in a translation product, namely shifts. The shifts in translation product are inevitable due to numbers of factors, such as cultural differences and unique language systems. The approach used to describe the findings is descriptive-qualitative by having textual data from the source language in English and target language in Indonesian. Having these comparisons will assist to focusing on the analysis of shifts happened in the translation. The data source is one of Sidney Sheldon’s famous novel Windmills of the Gods and its translation in Indonesian language Kincir Angin Para Dewa. There are 112 shifts found in the Indonesian translation, yet this article focuses on ten most representative translation shifts based on Catford’s (1974) translation shifts’ concepts, that is shift of level and shift of category. In this case, the article will take more portion to describe the clause shifts in particular.